NILAI-NILAI TOLERANSI DALAM DAKWAH PERSPEKTIF AL-QURAN - Afrizal El Adzim Syahputra (LP2M Universitas PTIQ Jakarta, 2023)
Among the characteristics of ideal da'wah is da'wah that prioritizes the values ​​of tolerance. The Quran as a guide for Muslims, especially for preachers, explains several values ​​of tolerance. Based on the results of research that the author has conducted, there are several values ​​of tolerance in preaching that originate from the Quran. First, dakwah with wisdom and good advice (QS. an-Nahl/16: 125). Second, dakwah with polite/gentle words. (QS. Taha/ 20: 43-44 and some fragments of verses in QS. an-Nahl/16: 125. Third, dakwah by respecting the beliefs of other believers (QS. al-An’am/6: 108 and QS. al-Kafirun/109: 1-6. Fourth, dakwah with humility (QS. as-Shu'ara '/26: 215). This research is a type of library research, namely research that object of study is library data form books and books of interpretation, as well as several other supporting references. It is hoped that this research will become one of the scientific treasures in the study of the interpretation of the Qur’an, especially the verses about the values ​​of tolerance in da’wah. Apart from that, it is hoped that the results of this research can become a reference source in preaching towards a pluralistic society, especially in the Indonesian context. Da'wah that prioritizes the values ​​of tolerance can eliminate divisions and disputes in social life